Estrategias de intervención psicopedagógica en estudiantes con autismo en el Centro de Educación Inicial Safari Kids. Riobamba - Chávez Yepez, Josseth Enrique (2025)
Autism spectrum disorder affects communication, social interaction, and behavior, requiring specialized psycho-pedagogical strategies for its treatment in the educational setting. In Ecuador, teacher training on ASD is limited, which hinders the teaching and implementation of intervention strategies. This problem is evident at the Safari Kids early childhood education center in Riobamba, where teachers face challenges in serving these students. Based on pre-professional practice at this institution, it was identified that the lack of training and access to adequate strategies affects the teaching-learning process. Therefore, this research seeks to determine the perceptions, knowledge, and strategies teachers use to design a guide that provides practical psycho-pedagogical intervention tools. The study reveals that, although teachers have acquired basic knowledge through experience and training, they lack specialized training to effectively address ASD. The proposed guide addresses this deficiency by providing adapted strategies in four key areas: social interaction, communication, restrictive behavior patterns, and body-motor development. These strategies strengthen teachers' pedagogical work and promote an inclusive educational environment, ensuring that every child with autism receives the necessary support for their comprehensive development